In order to solve using elimination, we need to be able to get rid of one variable, so that we can solve for the other. We need to subtract these two equations given from one another, or multiply the bottom equation by a negative and add them together.
(-5x + 6y = 8) - (-5x + 4y = 2)
(-5x + 6y = 8) + (5x - 4y = -2)
0x + 2y = 6
2y = 6
y = 3
Now that we know the value of one variable, we can take that value and plug it back into one of the original equations and solve for the value of the other variable.
-5x + 6y = 8
-5x + 6(3) = 8
-5x + 18 = 8
-5x = -10
x = 2
The solution to this system of equations is (2, 3).
Hope this helps!! :)
Answer: -7=0 --> Impossible
Step-by-step explanation:
2x-7+x-11= 3x-11
2x+x-7-11=3x-11
3x-18=3x-11
3x-18+11=3x
3x-7-3x=0
-7=0
Impossible
Answer:120 animals are in the pet store
Step-by-step explanation:
1,691,040,000
Hope this helps
Answer:
B: 5 + 4x < 24
Step-by-step explanation: